Multifunctional fluorescent carbon dots inhibit the invasiveness of lung cancer cells. (23rd August 2018) - Lin, Xiao Juan; Fan, Xiao Qing; Xiao, Sai Jin; He, Yan; Qi, Wen Jing; Hu, Ping Ping; Tan, Qun You; Tong, Xiao Yong; Huang, Cheng Zhi
Abstract : A new type of carbon dot (CD) is proposed, which has great potential to be an excellent fluorescent probe for bioimaging in vivo . Abstract : A new type of carbon dot (CD) is proposed, which has great potential to be an excellent fluorescent probe for bioimaging in vivo . Additionally, CDs can suppress the proliferation, migration and invasion of lung cancer cells by downregulating the protein expression of matrix metalloproteinase-2/9 and the activity of MMP-2.